TIME AND MATERIAL PRICING DALAM MENENTUKAN HARGA JUAL SERVICE DAN SUKU CADANG PADA PT SURYA TIMUR SAKTI JATIM DI SAMARINDA - -, Tri Wulandari (EKONOMIA, 2014)
In general, the selling price of products or services is determined by supply and demand in the market so in this case the cost to produce the product or service is not the only factor in determining the selling price. Due to consumer demand for products or services not easily determined by the management company in determining the selling price management will face a lot of uncertainty. PT Surya Sakti East Java is one of the service areas of its business sales service and spare parts of two-wheeled vehicles. Which problem is the lower price and selling price service service parts according to Time and Material Pricing Method with a selling price of service and spare parts services determined by the company. While the purpose of this study was to compare the selling price calculation service services according to the concept of full cost accounting information with Time and Material pricing method with selling services service and spare parts sales price according to the company